MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) PADA MATERI RANTAI MAKANAN KELAS V SDN 1 MOLIBAGU - Syabrina Gobel; Abdul Haris Panasi; Kudus; Gamar Abdullah; Isnanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research conducted by Syabrina Gobel in 2025 aims to improve student learning outcomes through the application of the Project Based Learning (PjBL) learning model on the food chain material in class V of SD Negeri 1 Molibagu, Bolaang Uki District, South Bolaang Mongondow Regency, North Sulawesi Province. The background of this research is the low learning outcomes of students in science subjects. The purpose of this study is to determine how the application of the PjBL model can improve the process and learning outcomes of students on the food chain material. This study uses a qualitative approach with the type of Classroom Action Research (CAR) involving 13 students and 1 class teacher as subjects in the 2024/2025 academic year. The focus of the research is on the process and learning outcomes of students. The instruments used include test sheets, observation, and documentation. Data collection techniques are carried out through observation of teachers and students, learning outcome tests, and documentation. Data analysis goes through three stages, namely data condensation, data presentation, and drawing conclusions. The research was carried out in three cycles, each of which includes the planning, implementation, observation, and reflection stages. The results of the study showed an increase from the category of Less Good (cycle I), Sufficient (cycle II), to Good (cycle III). In conclusion, the implementation of the PjBL model has been proven to be able to improve the process and results of student learning in the food chain material.